The biosynthetic pathway of coumarin and its genetic regulation in response to biotic and abiotic stresses - Wang, Yixue; Guan, Tiqing; Yue, Xianling; Yang, Jiashuo; Zhao, Xiaomin; Chang, Aixia; Yang, Changqing; Fan, Zhenjun; Liu, Keqiang; Li, Yiting (Frontiers in Plant Science, 2025)
Coumarins, a class of metabolites derived from the phenylpropanoid pathway, play critical roles in plant development and interactions with environmental factors. In recent years, numerous studies have revealed that catalytic enzymes, physiological conditions, and environmental stimuli collectively regulate coumarin metabolism in plants. This regulation is not only essential for normal growth and development, but also enhances plant resistance to environmental stresses. In this review, we summarize recent advances in understanding the roles of coumarins in plant development, the key enzymes and genes involved in their biosynthesis, and the genetic regulatory mechanisms that mediate plant responses to both biotic and abiotic stresses, including drought, salinity, UV radiation, and attacks by pathogenic bacteria and insects. The strategic implementation of multi-gene regulatory approaches holds great promise for enhancing plant stress tolerance and has significant potential applications in agriculture.